2014
DOI: 10.1111/bph.12867
|View full text |Cite
|
Sign up to set email alerts
|

Selective Na+/Ca2+ exchanger inhibition prevents Ca2+ overload‐induced triggered arrhythmias

Abstract: /Ca2+ exchanger (NCX) activity may play a crucial role in cardiac arrhythmogenesis; however, data regarding the anti-arrhythmic efficacy of NCX inhibition are debatable. Feasible explanations could be the unsatisfactory selectivity of NCX inhibitors and/or the dependence of the experimental model on the degree of Ca 2+ i overload. Hence, we used NCX inhibitors SEA0400 and the more selective ORM10103 to evaluate the efficacy of NCX inhibition against arrhythmogenic Ca 2+ i rise in conditions when [Ca 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
36
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 52 publications
13
36
1
1
Order By: Relevance
“…Therefore, the most important requirement for a NCX inhibitorbeyond potent blocking of NCX -is a minimal influence on the I CaL current. In previous studies of our laboratory (10,28,55,83,84), we reported that ORM-10103 effectively (Figure 7.) and selectively inhibits NCX in dog ventricular myocytes without influencing the I CaL current (figure not shown). Furthermore it was effective against triggered arrhythmias, namely it clearly decreased the amplitude of pharmacologically induced EAD and reduced the DAD incidence.…”
Section: Orm-10103mentioning
confidence: 64%
See 3 more Smart Citations
“…Therefore, the most important requirement for a NCX inhibitorbeyond potent blocking of NCX -is a minimal influence on the I CaL current. In previous studies of our laboratory (10,28,55,83,84), we reported that ORM-10103 effectively (Figure 7.) and selectively inhibits NCX in dog ventricular myocytes without influencing the I CaL current (figure not shown). Furthermore it was effective against triggered arrhythmias, namely it clearly decreased the amplitude of pharmacologically induced EAD and reduced the DAD incidence.…”
Section: Orm-10103mentioning
confidence: 64%
“…However, the lack of appropriate selectivity of the applied NCX inhibitors has made the data interpretation difficult and some important points are not fully clarified. The inotropic effect of selective NCX inhibition was expected however many studies reported lack of effect after selective NCX inhibition (28,30,31,78). Indeed, these compounds influenced the I CaL in some extent suggesting some reduction in the Ca 2+ influx which may counterbalance the inotropic effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental data on the antiarrhythmic effects of SEA0400 are sparse and contradictory, although mostly positive [47][48][49][50], while similar data for ORM-10103 have become available only very recently [41,51,52]. SEA0400 has a moderate inhibitory effect on the L-type Ca 2+ channels [40], while ORM-10103 has a minor effect on IKr; neither of these pleiotropic effects could substantially modulate the observed antiarrhythmic efficacy of the NCX inhibition.…”
Section: Regional Ischaemiamentioning
confidence: 99%